A review on recent trends and challenges of virtual immersive learning in engineering education - Muhammad Amin Azman,; Abdul Hadi Azman,; Asma Abu-Samah,; Muhamad Alias Md Jedi, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Teaching and learning process is facing new challenges in the twenty-first century and adaptations are needed to meet current situations and requirements. With the advancements of technologies in Industrial Revolution 4.0 (IR4.0) such as Augmented Reality (AR), 3D printing and Artificial Intelligence (AI), teaching and learning must adapt to new delivery methods and approaches. With the advancements in IR4.0, it is widely discussed how universities must stay relevant, and the introduction of the Future Ready Curriculum (FRC) framework is targeted to develop future-proof graduates. From Education 1.0, 2.0, 3.0, and 4.0, where the use of technology has been gradually increased in teaching and learning, it is important to establish new digitilized teaching delivery methods, hence immersive learning is introduced as one of the sub-elements in FRC under transformative delivery. Virtual “immersive learning” such as Virtual Reality (VR), Augmented Reality (AR), and Mixed Reality (MR) are example of immersive learning approaches, and leverage immersive technologies and techniques to create an environment where learners feel fully immersed in the subject matter, providing both the context and experience. This review paper covers the recent trends and challenges in employing virtual immersive learning for engineering education.